Which patients are assessed by lung cancer nurse specialists? A national lung cancer audit study of over 128,000 patients across England - Khakwani, Aamir; Hubbard, Richard B.; Beckett, Paul; Borthwick, Diana; Tod, Angela; Leary, Alison; White, John; Tata, Laila J. (Elsevier, 2016)
Background: Lung cancer nurse specialists (LCNS) are integral to the multidisciplinary clinical team, providing personalised physical and psycho-social interventions, and care management for people with lung cancer. The National Institute of Health and Care Excellence (NICE) recommend that all patients have access to a LCNS. We conducted a national study assessing whether there is variation in access to and timing of LCNS assessment.